COMPUTATIONAL EXPERIMENT AND ITS GRAPHICAL MODELING (Journal of Information Technologies in Education (ITE), 2011)
Article explains to the reader what “computational experiment” is and gives basic definitions of this notion. This article has a practical application because tells how and in what condition is better to use computational experiment and graphical modeling as one of the way of displaying the process or the event what has scientific importance and has to be under study.
Keywords: computational; demonstrable; event; examination; experiment; graphical; model; modeling; numeric; process